JAULAKAVACHARANA (HIRUDOTHERAPY): A UNIQUE PARA SURGICAL MEASURE - Ramesh, Kaundal; Omprakash, Sharma; Gaurav Garg, Kumar; Jyoti, Hiremath; Ashwani, Kumar (International Journal of Ayurveda and Pharma Research, 2015)
Raktamokshana (bloodletting) is a parasurgical procedure directed for the treatment of Raktajaroga (blood-borne diseases) along with many surgical diseases. Among different types of Raktamokshana, Leech therapy is practiced since ancient time. Acharaya Sushruta, the Father of Indian surgery has devoted an entire chapter on Jalaukavacharana for the purpose of bloodletting. It is considered as most unique and most effective method of bloodletting. It is safely indicated in all mankind including the patients having poor threshold to pain. The important advantage of Leech therapy is that it may be advised on those areas of body where other methods of bloodletting like Venesection (Siravedhan), cupping (Ghatiyantra) etc., are not possible. According to Ayurveda, Jalauka is used to expel out the vitiated blood safely, quickly and effectively. From modern perspective, the saliva of leech contains about hundred biological active substances. Leeches not only suck the impure blood but also leave behind their saliva, which contains enzymes that help to cure the disease. In present era, leech therapy has emerged as widely useful therapy in large number of diseases and is attracting the eyes of researchers all over the world.